Ideal cardiovascular health behaviors and factors prevent the development of hypertension in prehypertensive subjects. (17th November 2015) - Gao, Jingsheng; Sun, Hui; Liang, Xin; Gao, Ming; Zhao, Hongtao; Qi, Yanhong; Wang, Yanxiu; Liu, Ying; Li, Jinfeng; Zhu, Ying; Zhao, Yong; Wang, Wen; et al.
Abstract: Background : Seven ideal health metrics were defined by AHA to monitor cardiovascular health. This study aimed to investigate the impact of ideal cardiovascular health behaviors and factors on the development of hypertension in prehypertensive subjects. Methods : Thirty-two thousand eight-hundred and eighty-seven participants with prehypertension were included in the study after excluding for preexisting stroke, myocardial infarction or malignancy. Cox proportional hazards regression was used to calculate hazard ratios and 95% confidence intervals [CI] for the development of hypertension. Results : During a follow-up of 52.2 months, 15 500 prehypertensive participants developed hypertension. The cumulative incidence of hypertension decreased with the number of ideal health metrics increased. It was 78.61%, 71.08%, 63.15%, 56.07% and 61.62% in prehypertensive individuals carrying ≤1, 2, 3, 4 and ≥5 ideal health behaviors or factors, respectively. After adjustment for age, gender, family history of hypertension, alcohol consumption, resting heart rate, plasma triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and high-sensitivity C-reactive protein, the risk ratios of incident hypertension in the subjects who carried 2, 3, 4, and ≥5 ideal health metrics were 0.833 (95%CI: 0.789–0.880), 0.710 (95%CI: 0.672–0.749), 0.604 (95%CI: 0.568–0.642), and 0.581 (95%CI: 0.524–0.643), respectively, in comparison to those with ≤1 ideal health metric. A similar trend was also observed in male and female populations. Poor health metrics, including body mass index, diet (salt intake), physical activity, total cholesterol, and smoking, were predictors for the development of hypertension in prehypertensive individuals. Conclusion : Ideal cardiovascular health behaviors and factors are protective factors to prevent the progression from prehypertension to hypertension.